Beyond the Bell: After-School Programs and Educational Equity in Chinese Primary and Secondary Schools - Ping Wang; Feiye Wang; Yongbin Peng; Zhiyuan Li (SAGE Open)
In 2021, China introduced the “double reduction” policy, imposing strict regulations on shadow education and mandating the widespread implementation of after-school programs (ASPs). Against this backdrop, this study examines the role of ASPs in China’s compulsory education system from an equity perspective. By integrating school resources and family background, the study establishes a theoretical framework for understanding the factors influencing educational equity. Building upon this framework, it compares ASPs with shadow education and constructs a conceptual roadmap illustrating the impact mechanisms of ASPs on educational equity. To empirically test this framework, the study employs a Structural Equation Modeling (SEM) approach, analyzing questionnaire data from 1,458 primary and secondary school students in Shenzhen, China. The findings reveal that ASPs partially mediate the relationship between family cultural capital and students’ educational outcomes. Additionally, school resources play a significant role in enhancing student participation in ASPs. Notably, the educational outcomes of students engaged in ASPs are more strongly influenced by school-related factors. Compared to shadow education, school-organized and publicly funded ASPs have demonstrated greater effectiveness in promoting social equity. This study provides empirical evidence supporting the role of ASPs in replacing shadow education as a means to enhance educational equity. By verifying their effectiveness and specific impact pathways, the research offers valuable insights into the development of ASPs in China. Furthermore, it presents practical recommendations for global policymakers and educators committed to fostering educational equity.